THE MUSICAL SCORE: FROM PAPER TO THE ELECTRONIC MEDIUM - Ciprian Gabriel POP (Studia Universitatis Babeş-Bolyai. Musica)
The article presents several aspects regarding the evolution of the musical score. It touches upon a series of aspects of the development of musical notation support in consistency with technological evolution. The first part focuses on the traditional score, while the second one treats the close connection between the score and the electronic medium both from the point of view of its building and from the perspective of creation.